Picturing the tent helps, but we can actually solve this question using simple algebra and no knowledge of triangles.
The key is this function:
(b/h) = 2/√3
We want to get h by itself. First, multiply both sides by h:
b = h(2/√3) Now multiply both sides by the reciprical, (√3/2)
(√3/2) b = h
Therefore, the answer is C) h= b(√3/2)
Answer:
point form: (-2,7)
equation form: X = -2, Y = 7
Answer:
D
Step-by-step explanation:
Lets go case by case.
Given the roots, a factor will be part of the equation if for some of the roots the factor becomes null, i.e., equal to 0.
Is there any root that makes (x+3)=0? No, as it only becomes 0 for x = - 3 and -3 is not a root. So A NO!
Is there a root that makes (x-1)=0? No, as it only becomes 0 for x=1 and 1 is not a root. So B NO!
(x-4)=0 only for x=4, and as 4 is not a root, C NO!
The last, (x-3)=0 if x=3. As 3 is one of the roots, (x-3) is a factor of our equation!
D is the only correct option!
Hello there.
<span>How to solve -2 = -6 + 4v?</span>
<span><span>−2</span>=<span><span>4v</span>−6</span></span>
<span><span><span>4v</span>−6</span>=<span>−2</span></span>
<span><span><span><span>4v</span>−6</span>+6</span>=<span><span>−2</span>+6</span></span><span><span>4v</span>=4</span>
<span><span><span>4v/</span>4</span>=<span>4/4
</span></span><span>v=1</span>